Identifying the Role of Digital Self-Presentation in Adolescent Identity Formation - Morales, Luis; Torres, Camila (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to identify and interpret the role of digital self-presentation in shaping adolescent identity formation among Chilean youth within the broader context of social media engagement and self-concept development.Methods and Materials: A qualitative research design was employed using semi-structured, in-depth interviews with 33 adolescents aged 14–19 years from Santiago, Valparaíso, and Concepción, Chile. Participants were selected through purposive sampling to ensure diversity in gender, socioeconomic background, and social media usage. Data collection continued until theoretical saturation was reached. All interviews were conducted in Spanish, transcribed verbatim, and analyzed using thematic analysis with NVivo 14 software. The analysis involved open, axial, and selective coding to generate core themes reflecting participants’ lived experiences and meaning-making processes in digital environments. To enhance the study’s credibility, member checking and peer debriefing were performed.Findings: Three overarching themes emerged: (1) Digital Platforms as Identity Arenas, illustrating how adolescents strategically curate and manage their online personas; (2) Negotiating Authenticity and Social Expectation, revealing tensions between genuine self-expression and conformity to peer norms; and (3) Identity Development through Digital Interaction, emphasizing how feedback, role experimentation, and online reflection foster evolving self-awareness. The findings demonstrated that adolescents actively use social media to construct, test, and regulate their sense of self, while feedback mechanisms and social comparison dynamics significantly influence emotional well-being and self-esteem. Participants with stronger self-regulation and supportive family relationships displayed greater digital resilience and identity coherence.Conclusion: Digital self-presentation functions as both a developmental opportunity and a psychosocial challenge. It enables adolescents to explore diverse self-aspects and foster identity growth while simultaneously exposing them to social pressures and validation dependence. Conscious and reflective engagement in digital spaces can enhance identity integration and emotional balance in adolescence.